Use of Google Sites as A Web-Based Learning Media in Physics Learning for High School Teachers in Langsa City - Herliana, Fitria; Elisa; Syukri, Muhammad (Bahasa Indonesia, 2024)
Differentiated learning is a key component of the Merdeka Curriculum, which emphasizes the need for media that supports students in learning according to their individual characteristics and pace. As a result, teachers must develop suitable learning media. Platforms like Google Sites offer a free and accessible way for teachers to create materials and assessments that students can access anytime. Therefore, teacher training in using Google Sites to create web-based learning media is essential to support differentiated learning in the Merdeka Curriculum. The training was held at Muhammadiyah High School in Langsa City and was attended by 25 Physics teachers who were members of the Langsa City Physics Teachers Organization (MGMP). The effectiveness of the training was measured using a participant response questionnaire with a total of 14 statements, which included indicators of knowledge, skills, attitudes, and perceptions. The results of the training showed that teachers were satisfied, and there was an increase in teachers' knowledge, skills, and attitudes in using Google Sites as a web-based physics learning media. Teachers expressed optimism about using Google Sites as a tool that can facilitate student learning according to individual preferences.